Spinach (Spinacia oleracea) microgreen prevents the formation of advanced glycation end products in model systems and breads - Qian Zhou; Wenxin Liang; Jiaqian Wan; Mingfu Wang (Current Research in Food Science, 2023)
The formation of advanced glycation end products (AGEs) in daily diets poses a great threat to human health, since AGEs are closely related to some chronic metabolic diseases. In this study, we investigated the antiglycative capabilities of some popular microgreens in chemical model. Our data indicated that baby spinach (Spinacia oleracea) had the highest antiglycative activity during 4-wks incubation, with antioxidation being the main action route. Moreover, a bread model was set up to evaluate its antiglycative potential in real food model. The results showed that the fortification of baby spinach in bread significantly inhibited AGEs formation, with acceptable taste and food quality. Further study revealed that the antiglycative components were mainly distributed in leaves, which were separated via column chromatography and tentatively identified as chlorophyll derivatives. In summary, this study highlighted the antiglycative benefits of baby spinach which can be developed into healthy functional foods.